Natural science from the worldview of the Qur'an: an introduction - volume 1 - Hassan, Mohd. Kamal; Hassan @ Mohamed, Nor Jana; Zubir, Nazira; Husin, Abu Hassan; Mohd. Yusof, Mohd. Isa (Institut Terjemahan & Buku Malaysia (ITBM), 2021)
As the first of the three-volume work on natural science for secondary school students, volume one serves as the foundation for the subsequent volumes. The introduction and CHAPTER 1 lay the qur'anic worldview as the foundational premise in relation to the study and pursuit of natural science. It then embarks on explaining the nature of the discipline and how a scientific experience from a scientist is shared with and assessed by other scientists in the same field, which eventually renders the initial scientific experience into knowledge.